Sekolah Rendah Convent, 39000 Tanah Rata, Cameron Highlands, Pahang Darul Makmur - Zuelizry Ismail; Aisyah Abu Haris; Khairulidza Khalid; Mohammad Shukri Maslan; Nurul Ainin Parid Wardi; Syariza Shariff; Teh Norhashina Anoar (Skudai : Universiti Teknologi Malaysia, 2002)
Project Paper (Measured Drawing (Jabatan Senibina)) - Universiti Teknologi Malaysia, 2002